Systematic review of definitions and methods of measuring falls in randomised controlled fall prevention trials. - Hauer, K; Lamb, S; Jorstad, E; Todd, C; Becker, C (2006)
OBJECTIVE: to review systematically the range of case definitions and methods used to measure falls in randomised controlled trials. DESIGN/METHODS: a Cochrane review of fall prevention interventions was used to identify fall definitions in published trials. Secondary searches of various databases were used to identify additional methodological or theoretical papers. Two independent reviewers undertook data extraction, with adjudication by a third reviewer in cases of disagreement. SETTINGS: community-dwelling and institutionalised older persons. RESULTS: 90 publications met the predefined inclusion criteria. Of these, 44 provided no definition of the term fall. In the remainder, there were substantial variations in the definition and methods of measuring falls. Reporting periods ranged from 1 week to 4 years with only 41% using prospective data collection methods. CONCLUSION: the standard of reporting falls in published trials is poor and significantly impedes comparison between studies. The review has been used to inform an international consensus exercise to make recommendations for a core set of outcome measures for fall prevention trials.